Effect of thyroid-stimulating hormone in 68Ga-DOTATATE PET/CT of radioiodine-refractory thyroid carcinoma: a pilot study. Issue 5 (May 2018) - Almeida, Ludmila S.; Araújo, Maidane C.; Zantut-Wittmann, Denise E.; Assumpção, Lígia V.; Souza, Thiago F.; Silva, Cleide M.; Argenton, Juliana L.; Santos, Allan O.; Mengatti, Jair; Ramos, Celso D.; Etchebehere, Elba C.
Abstract : Background: Radioiodine-refractory thyroid carcinomas (RAIRs) are characterized by reduced expression of sodium–iodine symporter, rising serum thyroglobulin levels, and negative whole-body radioiodine scans. Interestingly, RAIRs continue to express somatostatin receptors and can be identified with 68 Ga-DOTATATE PET/CT imaging. Objective: The objective of this study was to compare lesion detectability in 68 Ga-DOTATATE PET/CT performed with elevated thyroid-stimulating hormone (eTSH) levels with suppressed thyroid-stimulating hormone (sTSH) levels. Patients and methods: Fifteen patients with RAIR were prospectively enrolled in this pilot study. All patients underwent two 68 Ga-DOTATATE PET/CT studies: with sTSH and with eTSH (after 30 days of levothyroxine withdrawal). All studies were blindly evaluated for differences pertaining to maximum standardized uptake values, detection of local recurrence, cervical lymph node (LN) metastases, cervical levels involved, distant LN metastases, lung metastases, and bone metastases. Reference standard consisted of fluorine-18-fluorodeoxyglucose PET/CT imaging, neck ultrasound, biopsy, and follow-up. Results: 68 Ga-DOTATATE PET/CT performed with both sTSH or eTSH was highly sensitive (91–100%) for detecting RAIR metastases. 68 Ga-DOTATATE PET/CT with eTSH detected a higher total number of lesions ( P =0.002), higher rate of cervical and distant LN metastases ( P =0.002 and 0.0313, respectively), and significantly higher maximum standardized uptake values for cervical and distant LN metastases ( P =0.0010 and 0.0078, respectively) when compared with sTSH. Conclusion: 68 Ga-DOTATATE PET/CT presents a high sensitivity in detecting metastatic lesions in patients with RAIR. Detectability increases with iodine-resistance, both with and without higher thyroid-stimulating hormone levels. These findings might improve staging and subsequent treatment planning, especially with radiolabeled somatostatin analogs.